PENGARUH FAKTOR BUDAYA DAN PERANAN GENDER PADA WIRAUSAHA PEREMPUAN DI UMKM - Rahmi Widiyanti; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Women play an important role in entrepreneurship even though the number offemale entrepreneurs is lower than male entrepreneurs. However, the distancebetween the two genders of entrepreneurs (male and female) varies due to theinfluence of different roles and stereotypes on entrepreneurial behavior. Thepurpose of this study is to find these differences, this paper analyzes the culturebetween male and female entrepreneurship from a cultural perspective in 35SMEs. The results of the study show that there is no clear relationship betweengender types and differences in entrepreneurship based on gender.